A bi-objective approach to routing and scheduling maritime transportation of crude oil. (June 2015) - Siddiqui, Atiq W.; Verma, Manish
Highlights: Routing and scheduling of crude oil tankers is considered from cost and risk perspective. A mixed-integer bi-objective optimization program is proposed. An expected consequence framework is used to estimate marine transport risk. The shortest (cheapest) route may not result in the lowest (mandatory) insurance premiums. Larger vessels should be used if risk is more important since it facilitates exploitation of the risk structure. Abstract: Maritime transportation, the primary mode for intercontinental movement of crude oil, accounts for 1.7 billion tons annually – bulk of which are carried via a fleet of large crude oil tankers. Although spectacular episodes such as Exxon Valdez underline the significant risk and tremendous cost associated with marine shipments of hazardous materials, maritime literature has focused only on the cost-effective scheduling of these tankers. It is important that oil transport companies consider risk, since the insurance premiums is contingent on the expected claim. Hence through this work, we present a mixed-integer optimization program – with operating cost and transport risk objectives, which could be used to prepare routes and schedules for a heterogeneous fleet of crude oil tankers. The bi-objective model was tested on a number of problem instances of realistic size, which were further analyzed to conclude that the cheapest route may not necessarily yield the lowest insurance premiums, and that larger vessels should be used if risk is more important as it enables better exploitation of the risk structure.